All‐Group IV Transferable Membrane Mid‐Infrared Photodetectors. (7th October 2020) - Atalla, Mahmoud R. M.; Assali, Simone; Attiaoui, Anis; Lemieux‐Leduc, Cédric; Kumar, Aashish; Abdi, Salim; Moutanabbir, Oussama
Abstract: Semiconductor membranes emerged as a versatile class of nanomaterials to control lattice strain and engineer complex heterostructures enabling a variety of innovative applications. With this perspective, herein this platform is exploited to tune simultaneously the lattice parameter and bandgap energy in group IV GeSn semiconductor alloys. As Sn content is increased to reach a direct bandgap, these semiconductors become metastable and typically compressively strained. It is shown that the relaxation in released membranes extends the absorption wavelength range deeper in the mid‐infrared. Fully released Ge0.83 Sn0.17 membranes are integrated on silicon and used in the fabrication of broadband photodetectors operating at room temperature with a record wavelength cutoff of 4.6 µ m, without compromising the performance at shorter wavelengths down to 2.3 µ m. These membrane devices are characterized by two orders of magnitude reduction in dark current as compared to as‐grown strained epitaxial layers. A variety of experimental tools and optimized calculations are used to discuss the crystalline quality, composition uniformity, lattice strain, and the electronic band structure of the investigated materials and devices. The ability to engineer all‐group IV transferable mid‐infrared photodetectors lays the groundwork to implement scalable and flexible sensing and imaging technologies exploiting these integrative, silicon‐compatible strained‐relaxed GeSn membranes. Abstract : All‐group IV GeSn membrane mid‐infrared photodetectors lay the groundwork to implement scalable and flexible sensing and imaging technologies exploiting the high‐yield and cost‐effectiveness enabled by silicon compatibility. This achievement is critical to develop large‐area, integrated sensors and imagers for label‐free chemical contrast in biosensing or environmental gas sensing, exploiting the 3–5 mm window of transparency in the Earth's atmosphere.